The role of nanocrystalline cellulose on the microstructure of foamed castor-oil polyurethane nanocomposites - Cordero, Andrés Ignacio (2015)
Nanocrystalline cellulose (CNC), obtained by sulphuric acid hydrolysis, was used to synthesize polyurethane foams (PUFs) based on a functionalized castor oil polyol and a Methylene diphenyl diiso- cyanate (MDI). Formulations with varying isocyanate index (FI) and NCO number were prepared. At 0.5 wt.%, SEM’s of the fractured surface underlined that the CNC acted both as a nucleation agent and as a particulate surfactant with cell geometries and apparent density changing selectively. The chemical structure of the PUF (FTIR) changed after the incorporation of CNC by a relative change of the amount of urea, urethane and isocyanurate groups. A low NCO number and isocyanate index contributed to the migration of the CNC to the Hard Segment (HS), acting as reinforcement and improving substantially the compressive mechanical properties (Ec and c improvements of 63 and 50%, respectively). For a high NCO number or isocyanate index, the CNC migrated to the Soft Segment (SS), without causing a reinforcement effect. The migration of the CNC was also detected with DSC, TGA and DMA, furtherly supporting the hypothesis that a low NCO number and index contributed both to the formation of a microstructure with a higher content of urethane groups.